Therapeutic Drug Monitoring and Outcome of Infliximab Therapy in Pediatric Onset Inflammatory Bowel Disease - Kolho, Kaija-Leena (Frontiers in Pediatrics, 2021)
Inflammatory bowel disease (IBD) with pediatric onset has become more prevalent during past decades. Thus, the number of patients with moderate to severe disease subtype treated with antagonists to tumor necrosis factor alpha (TNFα) has concurrently risen. Most pediatric patients initially respond to these drugs but will need dose escalation during the first year of therapy. As pediatric data regarding therapeutic drug monitoring during therapy with TNFα-blocker adalimumab are sparse, this review focuses on the literature on therapeutic drug monitoring of infliximab and how it may guide management.